Evaluation of child preference for dentist attire and usage of a camouflage syringe in reduction of anxiety - Mohammad Shakil Ahmad; Abdulsalam Alshami M. Alruwaili; Khalid Hussain A. Alruwaili; Abdullah Khalaf M. Alanazi; Layan Mohammed M. Alarjan; Abdulmajeed Mamdouh M. Alanazi; Naif Abdulrahman N. Aljunaydi; Abdulrahman Muharrab M. Alkhaldi; Meshari Farhan H. Alabdali; Faisal Fraih Alrashedi (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aimed to evaluate the effect of child-friendly dentist attire and camouflage syringes on reducing dental anxiety in children. Methods: A cross-sectional study was conducted with 120 pediatric patients aged 6 to 12 years. Participants were assigned to one of three groups: group A (child-friendly dentist attire), group B (camouflage syringe), or group C (control group). Child preference for dentist attire was assessed using a visual analog scale, while dental anxiety was measured using the Modified Child Dental Anxiety Scale and the Facial Image Scale. Results: The results showed a significant decrease in dental anxiety scores in both group 2 and group 3 compared to group 1 (P < 0.001). Children in group A exhibited a higher preference for child-friendly dentist attire [mean score: 8.7, standard deviation (SD): 1.2] compared to group 1 (mean score: 3.2, SD: 1.5) (P < 0.001). Similarly, children in group 2 showed a higher preference for a camouflage syringe (mean score: 8.5, SD: 1.3) compared to group 1 (mean score: 3.4, SD: 1.6) (P < 0.001). Conclusion: Child-friendly dentist attire and camouflage syringes were found to be effective in reducing dental anxiety among pediatric patients. These interventions were well received by children and their parents, highlighting the importance of considering child preferences in dental settings.